2019
DOI: 10.1371/journal.pone.0226548
|View full text |Cite
|
Sign up to set email alerts
|

Extending the use of the World Health Organisations’  water sanitation and hygiene assessment tool for surveys in hospitals – from WASH-FIT to WASH-FAST

Abstract: BackgroundPoor water sanitation and hygiene (WASH) in health care facilities increases hospital-associated infections, and the resulting greater use of second-line antibiotics drives antimicrobial resistance. Recognising the existing gaps, the World Health Organisations’ Water and Sanitation for Health Facility Improvement Tool (WASH-FIT) was designed for self-assessment. The tool was designed for small primary care facilities mainly providing outpatient and limited inpatient care and was not designed to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…Similarly, researchers have contextualized some monitoring tools in WaSH in HCF research. Maina et al [ 40 ] adapted and contextualized the WaSHFIT tool and developed WaSHFAST for the assessment of WaSH indicator performance in facilities beyond primary healthcare level. The authors developed a total of 65 WaSH in healthcare indicators relevant to monitoring WaSH in hospitals in limited resource areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, researchers have contextualized some monitoring tools in WaSH in HCF research. Maina et al [ 40 ] adapted and contextualized the WaSHFIT tool and developed WaSHFAST for the assessment of WaSH indicator performance in facilities beyond primary healthcare level. The authors developed a total of 65 WaSH in healthcare indicators relevant to monitoring WaSH in hospitals in limited resource areas.…”
Section: Discussionmentioning
confidence: 99%
“…The frame was guided by the logic framework (input, activities, output and impact), heuristic framework (agenda setting, formulation, implementation and evaluation) [ 37 ] and policy triangle (grounded in a political economy perspective and considers actors, context, process and content shape policymaking) [ 38 ]. The authors adapted the WaSHFIT conceptual framework [ 39 , 40 ]. It is a framework designed to help implementers identify risks in healthcare facilities and it provides practical tools and templates for managing WaSH and facilities.…”
Section: Methodsmentioning
confidence: 99%
“…Effective waste management of health care facilities is an often-neglected problem ( Harhay et al, 2009 ; Maina et al, 2019 ). There are major differences in healthcare waste and wastewater management around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there were scarce resources available to install new hand hygiene and waste disposal structures, especially in locations where they were absent. 3 …”
mentioning
confidence: 99%
“… 4 Our prepandemic survey suggested that these committees were inactive and poorly constituted. 3 The low status and awareness of infection prevention and control in the hospitals contributed to these committees being largely dormant. 4 However, from our interviews with health-care workers done during the COVID-19 pandemic in April, 2020, we found that these infection prevention and control committees are playing a crucial role in training medical staff on personal protective equipment use and infection prevention and control procedures (Maina M, unpublished).…”
mentioning
confidence: 99%